Modulations in movement by animals - Taylor, L (2018)
Movement is a fundamental aspect of life, which is intrinsically linked to almost every ecological and evolutionary process. Thus, a large fraction of an individual’s energy budget is invested in movement. Managing energy expenditure in relation to energy acquisition is critical for survival and is a primary focus for natural selection. Therefore, investigating how, when and why animals modulate their movement is crucial to understand behavioural ecology and, ultimately, the driving forces shaping evolution. The aim of my DPhil is to investigate how animals modulate their movement in response to their navigational capacity, the external presence of conspecifics and their internal reproductive state using two model species: the homing pigeon (Columba livia) and the African savannah elephant (Loxodonta africana). In Chapter 2, I report that homing pigeons modulate their wingbeat characteristics as a function of navigational knowledge, which suggests, for the first time, that navigation may have physical (biomechanical) manifestations. In Chapter 3, I show that pigeons increase their wingbeat frequency by c.18% when flying in pairs relative to flying solo. My results demonstrate that there is a substantial cost to flying together, and that the ultimate drivers of flocking, including predator protection and navigational knowledge, must outweigh these proximate costs. By contrast, in Chapter 4 I reveal that gestation, parturition and the presence of a neonatal calf has little impact on the movements of multiparous elephants, which could suggest that elephants’ unusually long gestation period evolved to facilitate an advanced stage of physical development. In my final data chapter, I show that reproductively active male elephants significantly increase their speed with age, suggesting that elephants increase energetic investments into reproduction as their probability of reproductive success increases. Overall, the results of my thesis provide key new insights into proximate and ultimate causes of movement and its modulation in animals.